Management of Pericardial and Pleural Effusion in a Dog with Pericardial Mass - Reddy Kype, Basava; Pentareddy Sagarika, Archana; Rajapantula, Mahesh (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The pericardium is a hard, fibroelastic sac that encloses the heart, with the ability to stretch appreciably in dogs tormented by pericardial effusion (PE) (Lorell and Braunwald, 1984). PE is characterized with the aid of a bizarre buildup of fluid in the pericardial space, at the same time as small volumes of PE won’t produce medical signs and symptoms, will increase in fluid volume and pressure can cause cardiac tamponade. The most common causes of PE in dogs are cardiac neoplasia, right sided heart failure, cardiac rupture, and idiopathic pericarditis and less commonly congenital pericardial disorders, trauma, or infectious origin. Pericardial tumors can make contributions to both pleural and pericardial effusions in dogs (Scollan et al., 2015). Blood analysis might also display mild anaemia and leukocytosis in cases regarding pericardial tumors, in particular haemangiosarcoma (Shaw and Rush 2007). The common physical findings in dogs with pericardial and pleural effusion encompass Muffled heart sounds, jugular vein distention, tachycardia, abdominal distension, abdominal respiration, poor pulse quality, ascites, dyspnea, and tachypnea (Kladakis et al, 2018). In lateral thoracic radiographs, the coronary heart often seems globoid or rounded. PE is now and again mistaken for dilated cardiomyopathy (DCM), and pleural effusion may also be seen on radiographs. Common ECG findings in dogs with PE encompass sinus tachycardia, ventricular arrhythmias, low voltage QRS complexes, ST phase elevation, and electrical alternans (Guglielmini et al., 2012). Echocardiography is a non-invasive and enormously effective diagnostic tool for detecting even small amounts of PE. The presence of PE itself complements visualization of the masses on the heart, because the fluid acts as a assessment medium (MacGregor et al., 2005). Echocardiography is considered the gold standard well known for diagnosing PE and formulating a therapeutic plan (Shaw and Rush, 2007). Treatment for pericardial and pleural effusion consists of pericardiocentesis and thoracocentesis, respectively, at the side of diuretic remedy. Chemotherapy may be considered in instances of cardiac neoplasia (Shaw and Rush, 2007). This communication reports successful management of pericardial and pleural effusion in a dog with pericardial mass.